Knowledge of Preconception Care and Associated Factors among Healthcare Providers Working in Public Health Institutions in Awi Zone, North West Ethiopia, 2019: Institutional-Based Cross-Sectional Study - Mahlet Million Bekele; Natnael Atnafu Gebeyehu; Mezgebu Mihret Kefale; Simachew Animen Bante (Journal of Pregnancy)
Background. Preconception care is a set of interventional care for the better maternal and childbirth outcome. Nevertheless, this area still faces implementation problems in most of the developing countries including Ethiopia. Objective. To assess the knowledge of preconception care and associated factors among healthcare providers working in public health institutions in Awi zone, North West Ethiopia. Method. An institutional-based cross-sectional study was conducted among 660 healthcare providers working in public health institutions in Awi zone, North West Ethiopia. A pretested structured self-administered questionnaire was used to collect the data from individual healthcare providers who were selected randomly using a multistage sampling technique. The data entry and analysis were conducted using SPSS version 25 software. Frequency, proportions, means, and standard deviations were used to describe the data. Candidate variables at bivariate logistic regression with a p value > 0.2 were moved to multivariable logistic regression models, and statistical significance was declared at p value < 0.05 with 95% confidence interval. Result. Among the total of 660 healthcare providers, 344 (52%) had good knowledge of preconception care. The odds ratio of having good knowledge of preconception care was high among healthcare providers working at hospitals [AOR=2.316, 95% CI: 1.900-5.528], using smartphones [AOR=3.177, 95% CI: 1.945-5.167], presence of preconception care guidelines at health institutions [AOR=3.166, 95% CI: 1.872-5.299], taking training on preconception care education and counseling [AOR=3.812, 95% CI: 2.241-6.581], taking training about human immune virus [AOR=4.911, 95% CI: 3.008-8.123], and attending training on increasing public awareness of preconception health and care [AOR=2.345, 95% CI: 3.922-5.488] which were independent predictors associated with knowledge of preconception care among healthcare providers. Conclusion. Healthcare providers’ knowledge of preconception care was low. Study participants working at hospitals, using smartphones, presence of preconception guidelines at health institutions, taking training on preconception education and counseling, taking training about human immune virus testing and management, and increasing public awareness of preconception care affect knowledge of health providers positively. The provision of updated training on preconception and linkage of internet service with health service should be enhanced among healthcare providers.